The Role of Indonesian Diplomatic Representatives in Resolving Cases of Persecution of Indonesian Migrant Workers in Malaysia - Melania, Chantika Wuragil Budhi (Universitas Sebelas Maret, 2021)
To achieve economic improvement and the welfare of its citizens, Indonesia is one of the countries that supports the practice of sending workers abroad or often referred to as Tenaga Kerja Indonesia (TKI). One of the leading destination countries for Indonesian migrant workers is Malaysia due to the geographical proximity and cultural similarities. However, the large number of Indonesian migrant workers in Malaysia is also proportional to the number of human rights violations experienced by Indonesian workers. Violations of rights such as embezzlement of salaries, physical torture, to murder often occur to Indonesian migrant workers in Malaysia. Based on the condition, the writer aims to analyze the role of the Indonesian government in protecting TKI who experience human rights violations in Malaysia through diplomatic representatives.